Returns from Indigenous Hunting in The Lowland Coastal Forests of West Papua, Benefits Threatened Wildlife Species - Freddy Pattiselanno; Johan F. Koibur (Institut Pertanian Bogor (IPB University), 2018)
We conducted a study in eleven villages in the West Papuan Bird's Head Peninsula to determine hunting returns from indigenous hunting in lowland coastal forests. In each town three collaborative hunters were recruited and trained to complete an information sheet for each hunting trip whether or not they were successful, and if so, how many individuals per species were killed and their common names. The results indicated that hunting returns during seven months of observations were 301 animals comprising of timor deer, wild pig, dusky pademelon, grizzled tree kangaroo and common spotted cuscus. The most commonly hunted were two non-native species-wild pigs and deer with a total of 11,475 kg of dressed weight harvested and which we valued at IDR230,625,000 (US17,435). A lowland forest ecosystem along the coast provides suitable habitats for the largest animals occurring within the sampled villages, like deer and wild pig. Hunting those species–deer and wild pig may provide conservation benefits to native species. There was little evidence of hunting native species or those of conservation concern. From ecology perspective, prey species and hunting return across the lowland coastal forest of West Papua has introduced wildlife species occurring at degraded habitat. Economically, the number of species hunted within the sampled village areas is determined by the hunter's assessment of profitability. Deer and wild pig are targeted because they provide a large amount of meat for both subsistence and sale purposes.